Pengaruh Kepemimpinan, Motivasi dan Lingkungan Kerja terhadap Disiplin Kerja Karyawan CV. Bumi Delta Makmur - Gusti Agung Anantabhoga Prubovsky Utameyasa; Bowo Santoso (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This research was conducted with the aim of analyzing the influence of leadership, motivation, and work environment on the work discipline of employees of CV. Prosperous Delta Earth. This research approach is included in quantitative research. The research population used is CV employees. Bumi Delta Makmur with a total of 32 respondents with a sampling technique using a saturated sample which makes the entire population the sample in the study. The source of research data comes from primary data which is directly obtained from respondents, namely employees of CV. Bumi Delta Makmur through the distribution of questionnaires. Data analysis techniques to process research data using data processing software Partial Least Square (PLS). Based on research data, it is revealed that leadership has no influence on employee work discipline, motivation has an influence on employee work discipline, and the work environment has an influence on employee work discipline at CV Bumi Delta Makmur. Keywords: Leadership; Motivation; Work environment; Work Discipline